(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Allergic rhinitis is an IgE mediated immunologic response of nasal mucosa to air born allergens and is characterized by watery nasal discharge, nasal obstruction, sneezing and itching in nose. Recurrence of allergic rhinitis is more common now a days. Etiological factor behind Allergic rhinitis is seasonal or perennial allergens. Genetic predisposition also plays an important part. Allergic rhinitis can be included under Pratishyaya in Ayurveda. Various medications are available in contemporary science; no drug ensures complete cure and chances of recurrences are high. In Ayurveda dietary preparation and yoga have enormous potential in reducing Allergic symptoms. Pippalyadi mamsarasa is mentioned in Ashtanga Hridaya Chikitsasthana which has Svasa hara, Kasa hara, and Prathisyaya hara properties and Kapalabhati clears airway reducing symptoms of Pratishyaya.